2011
DOI: 10.1590/s1413-78522011000300005
|View full text |Cite
|
Sign up to set email alerts
|

Tratamento artroscópico da luxação acromioclavicular aguda com âncoras

Abstract: OBJETIVO: Apresentar os resultados clínicos e radiográficos de uma série de casos com diagnóstico de Luxação Acromioclavicular (LAC) Aguda, tratados através da fixação coracoclavicular com âncoras por via artroscópica. MÉTODO: Vinte pacientes apresentando LAC com menos de 30 dias de evolução foram operados pela técnica da estabilização coracoclavicular com âncoras por via artroscópica. Duas âncoras metálicas com dois fios cada, foram inseridas no coracóide. Os fios foram amarrados sobre a clavícula passando po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
1
1
0
1
Order By: Relevance
“…In addition, 24 patients evaluated by this review that underwent arthroscopy showed an increase from 61 to 87 points on this scale 1 year after surgery [12]. Similar results were found by Cavinatto et al, who evaluated the functional outcomes of fourteen patients after arthroscopy, who had a mean Constant-Murley score of 94.79, ranging from 82 to 100 after 6 months post-operatively [20].…”
Section: Discussionsupporting
confidence: 84%
“…In addition, 24 patients evaluated by this review that underwent arthroscopy showed an increase from 61 to 87 points on this scale 1 year after surgery [12]. Similar results were found by Cavinatto et al, who evaluated the functional outcomes of fourteen patients after arthroscopy, who had a mean Constant-Murley score of 94.79, ranging from 82 to 100 after 6 months post-operatively [20].…”
Section: Discussionsupporting
confidence: 84%
“…This review included a total of 47 studies [1, 2, 4–9, 11, 13, 15–21, 23, 27–32, 34, 37–40, 43–46, 48–50, 52–62] (Table 1). Of these, 21 [2, 5, 6, 11, 18, 19, 27, 29, 38–40, 43–46, 48–50, 53, 55, 62] had information on associated intraarticular lesions and were included in the meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
“…24 Os procedimentos artroscópicos estão em constante expansão e apresentam vantagens, pois representam uma forma de tratamento minimamente invasiva. 25 Alguns estudos já demonstraram melhora nos escores clínicos, alta hospitalar precoce e retorno mais rápido às atividades diárias com o uso do tratamento artroscópico. 10,26 Apesar dessas vantagens, A técnica de artroscopia tem uma curva de aprendizado maior e é cara.…”
Section: Introductionunclassified